Supporting wellbeing through gender-inclusive practices : a practical guide for early years educators - Benham, Fifi (Routledge, 2024)
"Gender is a broad and complex concept, the impact of which can start even before a baby is born. It can be a source of restriction, but it is also a source of joy, and early years practitioners have a unique opportunity to empower new generations by creating gender inclusive environments where children feel confident and, above all, happy. This accessible and practical guide provides meaningful advice on how to improve and promote gender inclusion and wellbeing in early years settings. Chapters cover key areas, from gendered language and gender inclusive environments to trans and non-binary childhoods and encourage practitioners to reflect deeply on the way gender has impacted their own lives. The book provides: an overview and analysis of current guidance around gender equality and how this is integral to best practice and real-world practical tips and strategies that can be introduced right away, including advice for working effectively with parents. It includes book recommendations for settings and consideration of the language used in fairy tales and nursery rhymes, as well as signposting to further learning for practitioners. Guidance is offered on creating gender inclusive environments and making space for children to play around and make choices based on what brings them joy. Reflection points, practitioner reflections and case studies throughout bring theory to life. The early years presents the perfect time to encourage the exploration of identity as part of play, and the book enables practitioners to actively engage with this, to recognise and celebrate individuality, and to promote social, emotional, and mental wellbeing. This refreshing guide empowers practitioners to push boundaries in their setting to enable and maximise a positive approach to gender in practice. It is essential reading for all early years practitioners, as well as childminders and early childhood students"-- Provided by publisher.
"A Speechmark book" -- cover.
Keywords: Early childhood education.; Gender identity in education.; Gender identity in children.; School environment.; elektronické knihy; electronic books